ANALISIS LINGKUNGAN ORGANISASI DALAM MENUNJANG KINERJA ORGANISASI PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN LAMPUNG BARAT - M Fikri Akbar; Asmaria Asmaria; Dewi Susanty (e-JKPP, 2021)
The research method used in this research is descriptive qualitative method. The use of this method is to describe the Organizational Environment in Support of Organizational Performance at the Library and Education Service of West Lampung Regency, qualitatively examining how all data is obtained directly from informants in the field using interviews and document studies. The results showed that the organizational environment at the Department of Library and Education of West Lampung Regency is one of the causes of success in carrying out a job, because the organizational environment can affect workers, especially the organizational environment that is psychological in nature. The organizational environment at the West Lampung Regency Library and Readiness Service aims to provide maximum work comfort, so that employees in providing quality services, in the sense that if employees work and the results of the work get appreciation and recognition, then the work must be of quality. Supporting and inhibiting aspects in an effort to improve the organizational environment at the Library and Readiness Office of West Lampung Regency. These aspects can occur both internally and externally to the organization. Internal factors include elements contained in the body of the organization, namely the Library and Readiness Service of West Lampung Regency. Then the external factors of aspects that come from outside the West Lampung Regency Library and Readiness Service, such as local government, relevant agencies and the community. This occurs because a good organizational environment has been strived for, but it has not materialized as expected because there are still employees who are not fully comfortable with the existing organizational environment, such as air circulation, noise in the workplace.